Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1503/cmaj.200641
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in a 76-year-old man with initially negative nasopharyngeal swabs

Abstract: A 76-year-old man presented to a quaternary care hospital with a 6-day history of respiratory symptoms, fatigue and a fainting episode. The patient had a resolving postinfectious dry cough from an upper respiratory infection that occurred 3 months before presentation. He had hypertension, gastritis, diabetes, sciatica, a remote 30 pack-year smoking history and no history of recreational drug use. His medications included metformin and rosuvastatin. He worked as a professor and attended language classes.In earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The relationship between viral viability and symptom presentation was inconsistent. Some studies reported successful viral isolation from individuals who did not have symptoms at the time of sample collection [12,15,20,22], others isolated viable virus from individuals who were symptomatic at the time of sample collection [23,24], while other studies were unable to isolate virus from symptomatic individuals [13,25] (Table 3). There were inconsistent data available on viral load and/or RT-PCR cycle threshold (Ct) values and duration of viability, though a number of studies reported an upper limit on these measures for virus viability [12,22,23,2528].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between viral viability and symptom presentation was inconsistent. Some studies reported successful viral isolation from individuals who did not have symptoms at the time of sample collection [12,15,20,22], others isolated viable virus from individuals who were symptomatic at the time of sample collection [23,24], while other studies were unable to isolate virus from symptomatic individuals [13,25] (Table 3). There were inconsistent data available on viral load and/or RT-PCR cycle threshold (Ct) values and duration of viability, though a number of studies reported an upper limit on these measures for virus viability [12,22,23,2528].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these positive findings were from individuals with mixed levels of underlying comorbidities, and who presented with heterogeneous disease profiles, from mild symptoms to severe complications and death associated with infection with SARS-CoV-2. An additional impetus for taking a precautionary approach is the inconsistency from studies reporting on symptomatology and viable virus; while some studies were not able to successfully culture virus from asymptomatic or post-symptomatic individuals [13,14], others successfully cultured virus from individuals who were not symptomatic at the time of specimen collection [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…In cases where RT-PCR is initially negative, typical findings on CT may encourage maintenance of infection control mechanisms and prompt repeat testing. 8,24,25 In cases of high clinical suspicion but negative RT-PCR, a combination of repeated swab tests and CT imaging may be useful to reach the diagnosis and assist management. 9,26 With many countries beginning to ease lockdown restrictions and health care systems returning to near prepandemic levels of operation, it is important that radiologists remain vigilant to the typical COVID-19 CT imaging findings with the almost inevitable anticipated second wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether these systems are applicable to patients with incidental chest CT findings on an examination performed for another purpose. Particularly, a patient with typical CT findings in whom subsequent RT-PCR testing comes back negative poses a clinical dilemma-some of these cases eventually test positive bronchoalveolar lavage alone, 22 and this may be due to variability in test accuracy. Both systems are also deficient in providing recommendations for management and follow-up, unlike the widely adopted TI-RADS and CAD-RADS systems, and ultimately require more definitive testing with RT-PCR regardless of imaging findings.…”
Section: Discussionmentioning
confidence: 99%